Ethics at the Crossroads of Disciplines: Cognitive, Affect, and Literary Studies (KULT_online, 2023)
Patrick Colm Hogan’s book explores the interconnections between cognitive science, literature, and ethics. The author argues that a cognitive and affective understanding of the concepts of narrative and empathy may shed light on the process behind our moral thought. Drawing on interdisciplinary expertise, the book not onIy provides an important contribution to comparative literature and ethics but also advances cognitive and affective science.